Synthesis of Solar Panel Cooling Devices from A Mixture of Paraffin and Coconut Shell Activated Carbon - Nurhilal, Otong; Sekarwati, Dyah; Daniel, Fritz; Gultom, Noto Susanto; Setianto, Setianto (Teknotan: Jurnal Industri Teknologi Pertanian, 2026)
Coconut shell is a plantation waste that has the potential as an activated charcoal material due to its high lignocellulose content. Coconut shell activated charcoal (CSAC) is made through a carbonization process and chemical and physical activation. CSAC has been used in several applications such as adsorbents and electrode components. In this study, CSAC was used as a passive coolant mixture of Phase Change Material (PCM) from paraffin wax (PW). CSAC was made from charcoal that was carbonized at a temperature of 700oC and activated with ZnCl2. CSAC testing included specific surface area, diffraction patterns, functional groups and surface morphology. The results of the N2 isothermic test on CSAC obtained a specific surface area of 420.22 m2/g, a total pore volume of 0.22 cm3/g and an average pore diameter of 2.13 nm. The results of the XRD test showed the nature of CSAC with an amorphous polycyclic aromatic carbon structure. The results of the FTIR test showed aliphatic C–H functional groups derived from the remaining hydrocarbon chains of the cellulose and lignin structures. The C–O, O–H functional groups have been formed which indicates that activated carbon has been formed. The results of the SEM test showed a hollow surface with pore sizes dominated by mesoporous structures. Furthermore, CSAC was added to PCM-PW with a ratio of 5%:95% and 10%:90%. The test results showed an increase in the thermal conductivity of PCMCSAC. The use of SPPCMCSAC in solar panels has succeeded in reducing the surface temperature of solar panels by about 10oC and increasing efficiency by about 10%. The test results of SPPCMCSAC on solar panels demonstrate the ability of SPPCMCSAC to maintain solar panel efficiency.